2016
DOI: 10.1007/978-3-319-29406-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation and the Minority Suspect: Pathways to True and False Confession

Abstract: Eddie Torbio-Ruiz was asked to come to the police station in Reno, Nevada, voluntarily, to discuss allegations that he had sexually molested his girlfriend's two underage granddaughters. Although Eddie's native language was Spanish and he spoke English poorly, he was interrogated by English-speaking Detective Curtis Lampert. After asking a series of background questions, Lampert began an accusatory interrogation designed to cause Eddie to admit to the accusations against him. Throughout the interrogation, Lamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…Psychological research has demonstrated that the credibility of members of minority groups can be disadvantaged in comparison with that of their majority counterparts, even when the minority witnesses and suspects speak the same language as their interrogators, and the police interview is conducted in English (Villalobos & Davis, 2016). This bias can arise for various reasons.…”
Section: The Perceived Credibility Of English-speaking Outgroup Membersmentioning
confidence: 99%
“…Psychological research has demonstrated that the credibility of members of minority groups can be disadvantaged in comparison with that of their majority counterparts, even when the minority witnesses and suspects speak the same language as their interrogators, and the police interview is conducted in English (Villalobos & Davis, 2016). This bias can arise for various reasons.…”
Section: The Perceived Credibility Of English-speaking Outgroup Membersmentioning
confidence: 99%
“…Since the order was signed, federal and state agencies that provide direct public services have articulated language access plans with training, monitoring, and outreach components; translated vital documents and forms into commonly spoken languages; hired bilingual staff members; and increased their reliance on professional interpreters. Nevertheless, researchers continue to document linguistic inequalities in the criminal justice system, where people with limited English proficiency, like Natasha, are taken advantage of (Berk‐Seligson, 2009; Pavlenko, 2008; Villalobos & Davis, 2016; Wallace & Hernandez, 2017).…”
Section: Social Justice Pedagogy and Language Access: Theoretical Framentioning
confidence: 99%
“…The Court Interpreters Act of 1978 mandates the provision of an interpreter in court, but there is no equivalent law for investigative interviews. In many states, the right to an interpreter does not extend to custodial interrogations and people with limited English proficiency are interviewed without an interpreter (Villalobos & Davis, 2016). In the absence of an interpreter, L2 speakers may not understand their rights and the consequences of waiving them (all the more so when investigators speak faster on purpose).…”
Section: Teaching Legal Rights To Esl Students: a Research‐based Apprmentioning
confidence: 99%
See 2 more Smart Citations